Analısıs Pengaruh E-WOM, Citra Destinasi, Sikap dan Norma Subjektif terhadap Keinginan Melakukan Perjalanan ke Negara-Negara Asia - Lily Purwianti; Evelyn Claudia (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This study aims to determine the factors that influence the desire of travel intention people of Batam City to Asian countries. This research is useful to help all parties to know the factors that need to be considered in order to attract tourists to travel to Asian countries because it is considered to affect tourist intentions. This research is aimed at the people of Batam City who are interested in visiting Asian countries using 405 respondents who were collected through distributing questionnaires on social media. This research uses purposive sampling technique with data processing using SPSS version 24 program. The results of the study prove that the independent variables used such as E-WOM, destination image, attitude and subjective norms on the dependent variable, namely intention to travel have a significant positive effect.